(untitled) (Bangladesh Journal of Botany, 2015)
The effect of salt stress on enzyme activities of nine alfalfa cultivars at germination and seedling stage was studied. The activities of SOD, GR, POX and APOX were higher in salt tolerant and lower in salt sensitive cultivars. Results of the effect of salt stress on the SOD, GR, POX, APOX activities and MDA content may be used to select salt tolerance cultivars at the germination and seedling stages. SOD, GR, POX, APOX and MDA may play an important role in salt tolerant mechanisms in alfalfa. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21672 Bangladesh J. Bot. 43(2): 191-196, 2014 (September)